Safety and Efficacy of Third Kidney Transplantation in Ipsilateral Iliac Fossa. (July 2018) - Domagala, Piotr; van den Berg, T; Tran, K.; Terkivatan, T.; Kimenai, H.; IJzermans, J.; Pol, R.; Minnee, R.C.
Abstract : Abstract: Kidney retransplantation is an option for patients after graft loss returning to dialysis. However, evidence is lacking whether a third kidney transplant (KTx) in ipsilateral iliac fossa is safe and effective. The aim of this study is to review surgical outcome of third kidney transplantation in ipsilateral iliac fossa in comparison to first and second kidney transplants. Between 2010 and 2016 year, 2074 kidneys were transplanted in the Erasmus Medical Centre, Rotterdam and in University of Medical Centre Groningen. The databases were screened for adult third kidney transplantation in ipsilateral iliac fossa. The donor, recipient and surgical data were collected and analysed. The cohort was divided into three groups: first kidney transplantation (I KTx) (n=1744), second kidney transplantation in ipsilateral iliac fossa (II KTx) (n=44) and third kidney transplantation in the ipsilateral iliac fossa (III KTx) (n=7). We used one-way multivariate analysis of variance (MANOVA) to compare groups. There was significantly higher cold ischemia time in the III KTx group in comparison to I and II KTx group (543 min vs 167 min and 240 min respectively; p<0.001). Median operation time was significantly longer in II and III KTx group in comparison to I KTx group (205 min and 202 min vs 135 min respectively; p<0.001). Postoperative vascular and urological complications did not differ between groups. Median three months glomerular filtration rate was similar between groups. One- and five year graft survival did not differ between groups 96%, 89% (group I) 91%, 82% (group II) and group (III) 85%, 85% (p = 0.214) and (p = 0.116). One- and five year patient survival did not differ between groups 97%, 91% (group I) 100%, 90% (group II) and group (III) 100%, 100% (p = 0.796) and (p = 0.856). Third kidney transplantation in ipsilateral iliac fossa is feasible and viable with similar short and long-term results compared to first or second ipsilateral kidney transplantation.